Implementasi Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Mutu Sekolah Di UPT SPF SD Negeri 101776 Sampali - Dewi Nurhasanah Nasution (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to find out how the implementation of the principal's leadership in improving the quality of schools UPT SPF SD Negeri 101776 Sampali. The method used in this research is qualitative research, and is analyzed using a descriptive analysis approach that describes the implementation of the transformational leadership of school principals at UPT SPF SD Negeri 101776 Sampali. The data collection techniques use observation, interviews, and document studies. The results of this study reveal that the implementation of the principal's transformational leadership has been going well but is still not optimal. This can be seen from the school principal's ability to build a spirit of togetherness and discipline and motivate teachers and employees to work optimally. Principals dare to make changes through creative and innovative actions and are able to build organizational awareness among teachers and employees by developing an attitude of belonging and a sense of responsibility.